Guidelines for establishing Roots, Tubers and Banana (RTB) seed producers’ associations - Edson, S.; Ogero, K. (2025)
This publication provides practical, step-by-step guidance for establishing and strengthening seed producers’ associations for Roots, Tubers, and Bananas (RTB) crops. It outlines six key steps: identifying needs, defining objectives, drafting constitutions, conducting founding meetings, registering associations, and operationalizing them through governance, compliance, capacity building, and market linkages. The guideline emphasizes inclusion of women and youth, financial transparency, and digital recordkeeping. Illustrated with examples from the Tanzania Lake Zone Sweetpotato Seed Producers’ Association, it promotes collaborative action to enhance access to early generation seed, certification services, and markets. The framework aims to professionalize seed production and support sustainable, market-driven RTB seed systems across sub-Saharan Africa.